Poverty, voracity, and growth - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
This article investigates economic performance when enforceable property rights are missing and basic needs matter for consumption. It suggests a new view of the so-called voracity effect according to which windfall gains in productivity induce behavior that leads to lower economic growth. Taking into account that the rate of intertemporal substitution in consumption depends on the level of consumption, it is shown that 'voracious behavior' is situation-specific. It occurs when an economy is in decline and suffciently close to stagnation.
Keywords: O11; O13; D74; P48; 330; Economic growth; property rights; common pool resources; voracity; fractionalization; Erschöpfbare Ressourcen; Gemeingüter; Eigentumsrecht; Entwicklungsstufe; Wachstumstheorie; Theorie